2008
DOI: 10.1007/s00213-008-1087-x
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine augmentation of paroxetine CR for the treatment of refractory generalized anxiety disorder: preliminary findings

Abstract: Although conclusions are considered preliminary based on the relatively small sample size, our data do not support the addition of quetiapine to continued paroxetine CR for individuals with GAD who remain symptomatic after 10 weeks of prospective antidepressant pharmacotherapy and suggest that further research examining strategies for GAD refractory to antidepressants is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 38 publications
0
51
0
2
Order By: Relevance
“…23 The extent of quetiapine use to treat anxiety is unprecedented for an antipsychotic. Although several small randomized trials 24,25 were completed and published earlier, the first large randomized controlled trial (RCT) of quetiapine for anxiety was published in a peer-reviewed journal in 2010 26 followed by 4 others [27][28][29][30] in the following years. A systematic review 31 of RCTs of quetiapine for anxiety found it to be clinically efficacious for generalized anxiety; however, its overall tolerability was poor.…”
Section: Discussionmentioning
confidence: 99%
“…23 The extent of quetiapine use to treat anxiety is unprecedented for an antipsychotic. Although several small randomized trials 24,25 were completed and published earlier, the first large randomized controlled trial (RCT) of quetiapine for anxiety was published in a peer-reviewed journal in 2010 26 followed by 4 others [27][28][29][30] in the following years. A systematic review 31 of RCTs of quetiapine for anxiety found it to be clinically efficacious for generalized anxiety; however, its overall tolerability was poor.…”
Section: Discussionmentioning
confidence: 99%
“…While an augmentation study with a small sample size (6/11 patients completed) reported no additional benefit when quetiapine was added to paroxetine controlled release (Simon et al 2008), other studies have reported positive efficacy results for quetiapine as either monotherapy or adjunct therapy in patients with GAD (Adson et al 2004 ;Galynker et al 2005 ;Katzman et al 2008b). This study evaluated the efficacy and tolerability of quetiapine XR as once-daily monotherapy for GAD.…”
Section: Introductionmentioning
confidence: 93%
“…1i). Four studies 33,34,36,37 provided data on remission for 835 individuals. In these trials, the SGAs failed to demonstrate superiority to placebo (RR = 1.28; 95% CI, 0.96Y1.71; Fig.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Of the 5 included trials, 1 examined olanzapine, 33 2 examined risperidone, 34,35 and 2 examined quetiapine. 36,37 These studies included data on 912 patients and lasted 5 to 8 weeks. All studies included patients with a primary diagnosis of GAD, which the authors labeled refractory.…”
Section: Randomized Double-blind Placebo-controlled Studiesmentioning
confidence: 99%